Starvation and Climate Change—How to Constrain Cancer Cell Epigenetic Diversity and Adaptability to Enhance Treatment Efficacy - Gregg, Christopher (Frontiers in Ecology and Evolution, 2021)
Advanced metastatic cancer is currently not curable and the major barrier to eliminating the disease in patients is the resistance of subpopulations of tumor cells to drug treatments. These resistant subpopulations can arise stochastically among the billions of tumor cells in a patient or emerge over time during therapy due to adaptive mechanisms and the selective pressures of drug therapies. Epigenetic mechanisms play important roles in tumor cell diversity and adaptability, and are regulated by metabolic pathways. Here, I discuss knowledge from ecology, evolution, infectious disease, species extinction, metabolism and epigenetics to synthesize a clinically feasible approach to help homogenize tumor cells and, in combination with drug treatments, drive the extinction of cancer cells. Cycles of starvation and hyperthermia could help synchronize tumor cells, constrain epigenetic diversity and adaptability by limiting substrates and impairing the activity of chromatin modifying enzymes. Hyperthermia could also help prevent cancer cells from entering dangerous hibernation-like states. A pathway to a treatment paradigm is proposed that builds on the successes of fasting, hyperthermia and immunotherapy in cancer. Finally, I highlight the many unknowns, opportunities for discovery and the possibility that allele-specific epigenetic mechanisms pose a major barrier to cancer extinction and warrant deeper investigation.